2010
DOI: 10.1007/s00586-009-1267-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there a benefit to operating on patients (bedridden or in wheelchairs) with advanced stage cervical spondylotic myelopathy?

Abstract: Surgical treatment of cervical spondylotic myelopathy (CSM) aims to prevent or delay the progression of the disease. Many patients are diagnosed in advanced stages of the disease, presenting severe functional disability and extensive radiologic changes, which suggests clinical irreversibility. There are doubts about the real benefit of surgery in patients who are seriously ill, bedridden or in a wheelchair. The objective of the study is to evaluate the effects of surgical treatment in the clinical outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In general, the degree of gait disturbance increases with age in CSM patients. Some studies have presented results for recovery from severe gait disturbance using Nurick classification [21,22]. A majority of patients with a Nurick score of 5 who were either bedridden or in a wheelchair at diagnosis improved by at least one point after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the degree of gait disturbance increases with age in CSM patients. Some studies have presented results for recovery from severe gait disturbance using Nurick classification [21,22]. A majority of patients with a Nurick score of 5 who were either bedridden or in a wheelchair at diagnosis improved by at least one point after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Multilevel spinal stenosis and local kyphosis due to progressive disc degeneration are frequently seen in the elderly, exacerbating the condition 5,6) . Patients with advanced CSM tend to fall easily, resulting in them being bedridden or in a wheelchair because of the spinal cord disorder 7) . Surgical treatment is necessary before severe cord deterioration to prevent advanced myelopathy from decreasing their life expectancy and to improve clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors reported a mean 2.5-year follow-up period that is much shorter than our follow-up. One explanation for our observation may be that anterior cervical surgery is a highly effective operation even in severe cases where signs of upper motor neuron signs exist [24]. We acknowledge that the identification of predictors of better surgical outcomes is critical, as it may influence surgical decision making, the technique of the operation and patient expectations.…”
Section: Discussionmentioning
confidence: 93%